2019
DOI: 10.1093/eurpub/ckz128
|View full text |Cite
|
Sign up to set email alerts
|

Social mobility, accumulation of disadvantages and health. An analysis with retrospective data from the GSOEP (2002–14)

Abstract: Background Socioeconomic position (SEP) in different life stages is related to health-related quality of life (HRQoL). Yet, research on the relevance of life course processes is scarce. This study aims to analyse the association between accumulation of disadvantages, social mobility and HRQoL. Methods Analyses were conducted using population-averaged panel-data models and are based on data from the German Socio-Economic Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…a promotion into a higher-paid occupation), individuals have to cope with these new circumstances directly and promptly rather than over a longer period, which could increase levels of stress. Self-rated health Scotland Upward is beneficial Zang and de Graaf (2016) Happiness China None Hadjar and Samuel (2015) Life satisfaction United Kingdom Upward is detrimental Hadjar and Samuel (2015) Life satisfaction Switzerland None Clark and D'Angelo (2015) Life satisfaction United Kingdom Upward is beneficial Nikolaev and Burns (2014) Happiness USA Downward is detrimental Nikolaev and Burns (2014) Self-rated health USA Upward is beneficial, downward is detrimental Houle and Martin (2011) Depression USA Upward is beneficial (for subgroup) Tiffin et al (2005) Mental health England Downward is detrimental (for subgroup) Marshall and Firth (1999) Life satisfaction Ten countries None Intragenerational mobility Knöchelmann et al (2020) Self-reported physical health Germany Upward is beneficial, downward is detrimental (for subgroup) Much qualitative research has corroborated the idea of important mobility effects on individual wellbeing outcomes. Ingram (2011) interviewed working-class boys doing well at school and documented signs of their inner conflict, as boys attempt to diminish their affiliation to a working-class identity.…”
Section: Hypothesismentioning
confidence: 99%
“…a promotion into a higher-paid occupation), individuals have to cope with these new circumstances directly and promptly rather than over a longer period, which could increase levels of stress. Self-rated health Scotland Upward is beneficial Zang and de Graaf (2016) Happiness China None Hadjar and Samuel (2015) Life satisfaction United Kingdom Upward is detrimental Hadjar and Samuel (2015) Life satisfaction Switzerland None Clark and D'Angelo (2015) Life satisfaction United Kingdom Upward is beneficial Nikolaev and Burns (2014) Happiness USA Downward is detrimental Nikolaev and Burns (2014) Self-rated health USA Upward is beneficial, downward is detrimental Houle and Martin (2011) Depression USA Upward is beneficial (for subgroup) Tiffin et al (2005) Mental health England Downward is detrimental (for subgroup) Marshall and Firth (1999) Life satisfaction Ten countries None Intragenerational mobility Knöchelmann et al (2020) Self-reported physical health Germany Upward is beneficial, downward is detrimental (for subgroup) Much qualitative research has corroborated the idea of important mobility effects on individual wellbeing outcomes. Ingram (2011) interviewed working-class boys doing well at school and documented signs of their inner conflict, as boys attempt to diminish their affiliation to a working-class identity.…”
Section: Hypothesismentioning
confidence: 99%
“…Similarly, Hadjar and Samuel (2015) also find that upward mobility decreases life satisfaction, but only in the United Kingdom, not in Switzerland, and in neither country they find that downward mobility reduces life satisfaction. For the 'falling from grace' hypothesis, there is some evidence that downward mobility reduces wellbeing, including from different data sources from various countries (Kaiser and Trinh, 2021;Knöchelmann et al, 2020;Nikolaev and Burns, 2014;Tiffin et al, 2005). Most of these studies also find that upward mobility has salubrious effects on wellbeing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From semester fees to public transportation, some costs are involved, and these costs can affect older people differently depending on their financial situation. This intersection of inequality partially explains the differences in the health of older people (Corna, 2013;Knöchelmann et al, 2019). In addition to economic restrictions, bad health prevents people from participating in these types of programs.…”
Section: Theoretical Framework For Motivations and Learning In The Lamentioning
confidence: 99%